KREATIVITAS GURU DALAM MENGEMBANGKAN MATERI FIKIH DI MADRASAH ALIYAH MAMBAUL ULUM BATA-BATA PALENGAAN PAMEKASAN - Achmad Hamseh; Anwar Sa'dullah; Mutiara Sari Dewi (VICRATINA, 2020)
The teacher is an omportant faktor in ealizing the quality of learning. Therefore teachers must be able to use fiqh material and can develop based on their creativity so that in implementing learning can be achieved perfectly. The purpose of this study is to describe the creativity of teachers in developing fiqh munakahat material. The method used in this research is descriptive qualitative research by taking research in MA Mambaul Ulum Bata-Bata in palengaan District, Pamekasan Regensy. The results of this study indicate that the creativity of teachers in developing deverse material, some are developing journal-based material, developing audio-visual/video-based material, and some are developing library-based material. The internal supporting faktor in the teacher’s personal responsibility as a profession, the external supporting faktor is the availability of adequate infrastructure. Faktor internal inhibiting factors are lack of internet access that is in each corner of the clas and fasilities that are sometimes problematic.